Isu-Isu Kontemporer Pendidikan Islam: Tantangan Digitalisasi, Penguatan Karakter, dan Transformasi Pembelajaran di Era Society 5.0 - Nuruddin; Sukari (Lembaga Yasin AlSys, 2026)
The development of information and communication technology has brought significant changes to Islamic education and demands innovation to ensure its continued relevance to societal needs in the Society 5.0 era. Although digitalization, the use of artificial intelligence, changes in student characteristics, and the demands of twenty-first-century competencies create opportunities for learning development, these advances may also undermine moral and spiritual values and Islamic character if they are not accompanied by the strengthening of education based on Islamic teachings. This article aims to analyze contemporary issues in Islamic education, particularly the digitalization of learning, the strengthening of Islamic character, and the transformation of learning systems in the Society 5.0 era. The study employed a qualitative approach using a library research method through an analysis of books, national and international journal articles, and relevant educational policy documents. The data were analyzed using content analysis to produce a conceptual synthesis of the challenges and strategies for developing Islamic education. The findings indicate that digitalization has transformed the learning paradigm from teacher-centered to student-centered learning that is more flexible, collaborative, and technology-based. However, this transformation continues to face disparities in digital literacy, educators’ limited technological competence, the misuse of digital media, and the degradation of students’ character due to exposure to uncontrolled information. Therefore, the transformation of Islamic education needs to be directed toward integrating digital technology with Islamic values through character strengthening, the enhancement of teachers’ competencies, the development of adaptive curricula, and the implementation of innovative, humanistic learning oriented toward twenty-first-century competencies. This study concludes that Islamic education in the Society 5.0 era is required not only to adapt to technological developments but also to continue serving as a foundation for developing students’ morals, character, and spirituality. Synergy among technology, Islamic values, and learning innovation constitutes an essential foundation for realizing excellent, adaptive, and globally competitive Islamic education.